An Omalizumab Biobetter Antibody With Improved Stability and Efficacy for the Treatment of Allergic Diseases - Liu, Peipei; Pan, Zhongzong; Gu, Chunyin; Cao, Xiaodan; Liu, Xiaowu; Zhang, Jianjian; Xiao, Zheng; Wang, Xueping; Guo, Haibing; Ju, Dianwen; Deng, Su-Jun (Frontiers in Immunology, 2020)
The critical role of IgE in allergic diseases is well-documented and clinically proved. Omalizumab, a humanized anti-IgE antibody, was the first approved drug for the treatment of allergic diseases. Nevertheless, omalizumab still has some limitations, such as in stability and dosage restriction in clinical application. In this study, we sought to generate an omalizumab biobetter antibody with the potential to improve the stability and treat a broad patient population. We removed two aspartic acid isomerization hotspots in CDRs of omalizumab to improve antibody candidate’s stability. Meanwhile, several murine amino acids in the framework region of omalizumab were replaced with human source to reduce the potential immunogenicity. Yeast display technology was then applied to generate antibody candidate with high affinity to IgE. Moreover, YTE mutation in Fc fragment was introduced into the candidates for extending their serum half-life. AB1904Am15, a lead candidate, showed desired biophysical properties and improved stability, exhibited higher affinity and elevated potency in vitro, demonstrated prolonged half-life in human FcRn transgenic mouse, and enhanced in vivo efficacy in cynomolgus monkey model of asthma. This is the first reported study showing the efficacy of anti-IgE antibody in a cynomolgus monkey model of asthma. Overall, our results suggested that AB1904Am15 might be a biobetter therapeutic candidate for the treatment of allergic diseases in the future.